VALIDITAS E-BOOK INTERAKTIF BERBANTUAN HEYZINE FLIPBOOKS PADA MATERI KLASIFIKASI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS - Fani Puspitasari; Mawartiningsih, Lilik (JPB - Jurnal Pendidikan Biologi, 2024)
The purpose of this study was to determine the validity of interactive e-books assisted by Heyzine Flipbooks on classification material to improve critical thinking skills. This type of research is research and development (R&D) using the 4D development model (Four-D models). Data collection was carried out using an instrument in the form of a validation questionnaire distributed to material, media and language expert validators. This research and development produced an interactive e-book assisted by Heyzine Flipbooks to improve valid critical thinking skills based on the achievement of material, media, and language aspects. This interactive e-book design contains features such as the addition of links, images, videos, audio, and the web so that the Heyzine Flipbooks-assisted e-book contains more information with diverse and interactive sources. As for the results of data analysis validation by material, media, and language experts, interactive e-books assisted by Heyzine Flipbooks to improve critical thinking skills developed have met the criteria with the results of the average percentage score from validators of 81.81% in material aspects, 81.20% in media aspects, and 81.47% in language aspects so that it can be stated that interactive e-books assisted by Heyzine Flipbooks show a valid category and are feasible to use with revisions to learning.